EVALUASI KOMITMEN DAN KEBIJAKAN SISTEM MANAJEMEN KESELAMATA DAN KESEHATAN KERJA (K3) SEBAGAI UPAYA PERLINDUNGAN TERHADAP TENAGA KERJA - Naldi Nurwahyudi Siagian; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Occupational Health and Safety (K3) is our effort to create a healthy and safe work environment, so as to reduce the probability of work accidents/illness due to negligence which result in demotivation and work productivity deficiencies. According to the Republic of Indonesia's Basic Health Law no. 9th 1960 Chapter I Article II, Occupational Health is a health condition that aims to make the working community obtain the highest degree of health, both physically, spiritually and socially, with efforts to prevent and treat diseases or health problems caused by work and the work environment and diseases. general. The Occupational Safety and Health Management System (SMK3) is part of the company's overall management system in order to control risks related to work activities in order to create a safe, efficient and productive workplace (PP No. 50 of 2012). This research method uses the method of collecting data in this study using the literature review method (literary study)